2015
DOI: 10.1177/1077559515617019
|View full text |Cite
|
Sign up to set email alerts
|

Child Maltreatment and Migration

Abstract: Differences in the prevalence of CM across ethnographic origins are at least partially related to socioeconomic and ecologic risk factors. The distribution of risk factors may vary depending on the contexts of migration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 58 publications
0
22
0
Order By: Relevance
“…There were four studies in the USA [47][48][49][50], three in the UK [51][52][53], two in Hong Kong [54][55] two in Taiwan [56][57], and two in Germany [58,59]. There was one study in Denmark [60], the Netherlands [61], Switzerland [62], Japan [63], Suriname [64], Saudi Arabia [65], Israel [66], South Africa [67], and Hungary [68]. In the Balkans study [46], eight met eligibility criteria based on the number of types of maltreatment studied: Albania, Bosnia & Herzegovina, Bulgaria, Croatia, the Former Yugoslavian Republic of Macedonia, Greece, Romania, and Serbia; in general for our purposes, we treat these as one study.…”
Section: Systematic Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…There were four studies in the USA [47][48][49][50], three in the UK [51][52][53], two in Hong Kong [54][55] two in Taiwan [56][57], and two in Germany [58,59]. There was one study in Denmark [60], the Netherlands [61], Switzerland [62], Japan [63], Suriname [64], Saudi Arabia [65], Israel [66], South Africa [67], and Hungary [68]. In the Balkans study [46], eight met eligibility criteria based on the number of types of maltreatment studied: Albania, Bosnia & Herzegovina, Bulgaria, Croatia, the Former Yugoslavian Republic of Macedonia, Greece, Romania, and Serbia; in general for our purposes, we treat these as one study.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Fourteen studies measured all five maltreatment types [47][48][49][50][51]53,[56][57]61,[64][65][66][67][68]. Of nine studies measuring four maltreatment types, seven omitted EDV [46,52,[58][59][60][62][63], and two omitted sexual abuse [54][55]. Eleven studies measured prevalence throughout childhood and in the past year; nine measured prevalence through childhood only, and three measured past year incidence only.…”
Section: Systematic Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, coming from a migration background might also have an impact. Migration itself can be a very stressful [27], moreover, Schick et al [28] found that a migration background was a risk factor of child maltreatment. Additionally, the prevalence in mental disorders differed between migrants and non-migrant in a study by Gaber et al [29].…”
Section: Introductionmentioning
confidence: 99%